2014
DOI: 10.1161/circinterventions.113.000978
|View full text |Cite
|
Sign up to set email alerts
|

Does Routine Pressure Wire Assessment Influence Management Strategy at Coronary Angiography for Diagnosis of Chest Pain?

Abstract: Background-The use of coronary angiography (CA) for diagnosis and management of chest pain (CP) has several flaws.The assessment of coronary artery disease using fractional flow reserve (FFR) is a well-validated technique for describing lesion-level ischemia and improves clinical outcome in the context of percutaneous coronary intervention. The impact of routine FFR at the time of diagnostic CA on patient management has not been determined. Methods and Results-Two hundred patients with stable CP underwent CA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(173 citation statements)
references
References 26 publications
9
158
2
4
Order By: Relevance
“…23 This may be in part because the use of adenosine in the catheterization laboratory has infrequently been associated with complications. [24][25][26] On the basis of the findings observed in our study, iFR, which allows for lesion assessment without the use of adenosine, has the potential to increase the use of physiologically guided assessment among patients with coronary artery disease, the majority of whom still undergo angiographic assessment of lesion severity.…”
Section: Discussionmentioning
confidence: 76%
“…23 This may be in part because the use of adenosine in the catheterization laboratory has infrequently been associated with complications. [24][25][26] On the basis of the findings observed in our study, iFR, which allows for lesion assessment without the use of adenosine, has the potential to increase the use of physiologically guided assessment among patients with coronary artery disease, the majority of whom still undergo angiographic assessment of lesion severity.…”
Section: Discussionmentioning
confidence: 76%
“…study evaluated the clinical implications of routine FFR measurement in all coronary arteries and demonstrated an important influence on planning patient management 23. In the RIPCORD study, ≈16% of lesions with percentage of diameter stenosis (%DS) <50% showed FFR <0.80.…”
Section: Introductionmentioning
confidence: 99%
“…reclassification of individual management in a large proportion of patients: 26% in RIPCORD 5 and 47% in R3F. Second, reclassification of the treatment strategy was achieved in all groups of treatment.…”
Section: Circ Cardiovasc Intervmentioning
confidence: 93%
“…Despite this evidence, the role of FFR in patients referred for a diagnostic angiography, although of potential critical importance for patient management, was unknown before the publication of the RIPCORD 5 and R3F studies. 6 The RIPCORD 5 study was conducted in 10 centers in the United Kingdom and included 200 patients referred for a coronary angiography.…”
Section: Article See P 248mentioning
confidence: 99%
See 1 more Smart Citation